An Essential Memory Trace Found. - Thompson, Richard F. (Behavioral Neuroscience, 2013)
I argue here that we have succeeded in localizing an essential memory trace for a basic form of associative learning and memory--classical conditioning of discrete responses learned with an aversive stimulus--to the anterior interpositus nucleus of the cerebellum. We first identified the entire essential circuit, using eyelid conditioning as the model system, and used reversible inactivation, during training, of critical structures and pathways to localize definitively the essential memory trace. In recognition of the 30th anniversary of Behavioral Neuroscience, I highlight 1 paper (Tracy, Thompson, Krupa, & Thompson, 1998) that was particularly significant for the progress of this research program. In this review, I present definitive evidence that the essential memory trace for eyelid conditioning is localized to the cerebellum and to no other part of the essential circuit, using electrical stimulation of the pontine nuclei-mossy fibers projecting to the cerebellum as the conditional stimulus (CS; it proved to be a supernormal stimulus resulting in much faster learning than with any peripheral CS) and using an electrical stimulus to the output of the cerebellum as a test, which did not change. Pontine patterns of projection to the cerebellum were confirmed with retrograde labeling techniques.